Apical periodontitis and periodontal disease increase serum IL-17 levels in normoglycemic and diabetic rats - Cintra, Luciano Tavares Angelo [UNESP]; Samuel, Renata Oliveira [UNESP]; Azuma, Mariane Maffei [UNESP]; Ribeiro, Clicia Pereira [UNESP]; Narciso, Luis Gustavo [UNESP]; Felix de Lima, Valeria Marcal [UNESP]; Sumida, Doris Hissako [UNESP]; Coclete, Gilberto Aparecido [UNESP]; Dezan Junior, Eloi [UNESP]; Gomes Filho, João Eduardo [UNESP] (Springer, 2014)
This study aimed to evaluate the influence of apical periodontitis (AP) and/or periodontal disease (PD) on serum interleukin-17 (IL-17) levels in a rat model of diabetes mellitus (DM).Eighty male Wistar rats were divided into eight groups of ten animals each: normoglycemic, AP, PD, AP+PD, DM, DM+AP, DM+PD, and DM+AP+PD. DM was induced using streptozotocin, AP by dental pulp exposure to the oral environment, and PD by periodontal ligature. The animals were sacrificed after 30 days, and venous blood samples were collected via cardiac puncture to determine the serum IL-17 and neutrophil levels. The maxillae were dissected and processed for radiographic analysis. The periapical lesion areas were quantified in pixels. The total assessed values were tabulated according to each experimental group and were statistically analyzed using Spearman's correlation and Kruskal-Wallis test (p < 0.05).A significant difference in the serum IL-17 levels was observed between the groups without oral infections and the groups with AP+PD-associated lesions, regardless of the presence of DM (p < 0.05). Diabetes increased the neutrophil levels, regardless of the presence of oral infection. However, a combination of two oral infections increased the neutrophil levels in DM rats (p < 0.05). The level of bone resorption lesions was greater in DM rats than in normoglycemic rats (p < 0.05).The combination of AP and PD increased the serum IL-17 levels in DM and normoglycemic rats and increased the neutrophil levels in DM rats. Diabetes increased the neutrophil levels and bone resorption in rats.AP is capable of potentiating systemic inflammatory changes when associated with PD, and increases in blood glucose can accelerate the pathogenesis of oral infections.
Keywords: Interleukin-17; Apical periodontitis; Periodontal disease; Neutrophil; Diabetes